Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpsyt.2020.561657
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of Social Service Providers and Families of Children With Autism or Development Delays During the COVID-19 Pandemic—A Community Case Study in Hong Kong

Abstract: Background: Hong Kong is one of the earliest cities to have hampered by the COVID-19. When preventive public health measures are enforced, specific groups, who have already been facing inequality before the outbreak, are likely to become more overlooked and vulnerable.Aim: This community case study aims to describe the additional needs of families of children with autism spectrum disorder and other developmental issues, as well as unexpected difficulties and challenges social service professionals encountered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 45 publications
(57 reference statements)
3
29
0
14
Order By: Relevance
“…Increased stress levels and lower levels of well-being of parents of children with ASD were confirmed by a large number of studies [29] in comparison with parents of neurotypical children or children with other forms of disability [30][31][32][33]. Furthermore, it could often lead to burnout, depression, and psychological and physical breakdown, a condition that is exacerbated by deficits in services and general childcare [26,27,34].…”
Section: Introductionmentioning
confidence: 90%
“…Increased stress levels and lower levels of well-being of parents of children with ASD were confirmed by a large number of studies [29] in comparison with parents of neurotypical children or children with other forms of disability [30][31][32][33]. Furthermore, it could often lead to burnout, depression, and psychological and physical breakdown, a condition that is exacerbated by deficits in services and general childcare [26,27,34].…”
Section: Introductionmentioning
confidence: 90%
“…Overall, several participants reported that stressful time spent at home contributed to relationships within the household becoming strained or more severely disrupted. Indeed, international findings report that social service providers have had to adapt the content of their interventions during the pandemic and increasingly target emotional coaching, activation, and parent support [24].…”
Section: Negative Outcomesmentioning
confidence: 99%
“…Clearly, the pandemic conditions have had pervasive effects on the lived experiences of the global autism community. Notably, several studies are now showing that families have at least partly lost access to healthcare and support services [22][23][24][25] causing worries about the potential long-term effects on children's emotional health as well as educational and developmental progress [23]. Nevertheless, adhering to prevention measures and guidelines, many care services changed the structure or adapted the content of treatment protocols to move online [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study also suggested that promoting preventive measures can alleviate the fear and confusion of the population and protect mental health in China[ 21 ]. Therefore, understanding the adoption of preventive behaviours at the household level and exploring inequalities within families are necessary for governments in China and other countries [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%